Exploring Students’ Critical Thinking and Curiosity: A Study on Problem-Based Learning with Character Development and Naturalist Intelligence - Suhirman, Suhirman; Ghazali, Ihwan (International Journal of Essential Competencies in Education, 2022)
This study aimed to investigate the impact of problem-based learning with a focus on character development and naturalist intelligence on critical thinking (CT) abilities and curiosity of students. The study was conducted in a school in the city of Mataram - Indonesia, utilizing a 3x2 treatment by level design. Two groups of students, categorized as having high or low naturalist intelligence, were exposed to three different treatments: problem-based learning with character development (PBL-CD), problem-based learning, and regular learning. Data regarding the students' naturalist intelligence and CT abilities were collected through tests, while information on their curiosity was obtained through observation sheets and self-assessment. Statistical analysis using MANOVA at a significance level of 0.05 was performed. The findings revealed that: (a) PBL-CD had a positive impact on students' CT abilities and curiosity; (b) the naturalist intelligence did not significantly influence students' CT abilities and curiosity; and (c) there was no significant impact observed on students' CT abilities and curiosity when examining the interaction between PBL-CD and naturalist intelligence. Thus, PBL-CD presents itself as a viable strategy to cultivate students' critical thinking skills and inquisitiveness, offering an alternative pathway in routine learning in the classroom.